The science of obesity - May, W; Goedecke, J H; Conradie-Smit, M (South African medical journal, 2025)
KEY MESSAGES • Obesity arises from a complex interplay of genetic, biological, behavioural, psychosocial and environmental factors.• Obesity has a strong genetic component, with twin studies indicating a 50 - 80% concordance in body mass index (BMI) and regional fat distribution. A Swedish study on identical twins raised apart found no correlation between BMI and their adoptive families but a strong correlation with their biological twin, despite being raised in separate households.• The regulation of appetite, body weight and energy balance is highly complex, governed by a network of hormonal signals from the gut, adipose tissue and other organs, as well as neural signals that shape eating behaviours. Many of these signalling pathways are disrupted in people living with obesity.• Since body weight is homeostatically regulated, weight loss triggers physiological adaptations that promote weight regain. These include a decrease in energy expenditure, and hormonal changes that enhance appetite while reducing satiety.• Adipose tissue influences the central regulation of energy homeostasis, and excess adiposity can become dysfunctional, with production of proinflammatory cytokines and associated metabolic health complications.• Individual variations in body composition, fat distribution and function result in a highly variable threshold at which excess adiposity begins to negatively affect health.• Emerging research in obesity science has widened to include brown fat, the gut microbiome, immune system regulation, and the intricate mechanisms that regulate body weight.• Obesity can be classified as primary, secondary and genetic obesity.• In the current management of primary obesity, prevention (the path in) and treatment (the path out) need to be distinctly separated.• Effective primary obesity treatment requires an integrated approach that addresses the non-modifiable cause (increased appetite) together with modifiable contributors (poor diet quality, increased stress, poor sleep, reduced physical activity and increased sedentary behaviour). Behavioural modification and psychological support provide additional benefit.• Effective treatment in genetic and secondary obesity requires treatment of the underlying causes along with modification of the contributors.